2007
DOI: 10.1210/en.2007-0898
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Amylin and Peptide YY[3–36] in Obese Rodents: Anorexigenic Synergy and Weight Loss Additivity

Abstract: Circulating levels of the pancreatic beta-cell peptide hormone amylin and the gut peptide PYY[3-36] increase after nutrient ingestion. Both have been implicated as short-term signals of meal termination with anorexigenic and weight-reducing effects. However, their combined effects are unknown. We report that the combination of amylin and PYY[3-36] elicited greater anorexigenic and weight-reducing effects than either peptide alone. In high-fat-fed rats, a single ip injection of amylin (10 microg/kg) plus PYY[3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 53 publications
1
47
0
1
Order By: Relevance
“…The present studies extend emerging literature, where additive or synergistic interactions are reported for amylin in 32 and leptin), 40,41 to include small molecule agents that act via classic neurotransmitters. Consistent with the results reported here, co-administration of the amylin agonist pramlintide with sibutramine or phentermine in a clinical trial has recently been reported to result in increased weight loss in obese subjects.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The present studies extend emerging literature, where additive or synergistic interactions are reported for amylin in 32 and leptin), 40,41 to include small molecule agents that act via classic neurotransmitters. Consistent with the results reported here, co-administration of the amylin agonist pramlintide with sibutramine or phentermine in a clinical trial has recently been reported to result in increased weight loss in obese subjects.…”
Section: Discussionsupporting
confidence: 67%
“…[28][29][30] Intermeal interval is governed by a complex cascade of post-ingestive, neural, endocrine and metabolic signals. In rodents, amylin has also been shown to synergize with at least two signals (CCK 31 and PYY ) 32 Co-administration of amylin and phentermine JD Roth et al neurohormonal signals is unknown, but could contribute to amylin þ phentermine protraction of the intermeal interval. The generation of plasma hormonal profiles in amylin þ phentermine-treated rats before and after the consumption of a meal, and/or the assessment of food intake in the context of a sham feeding preparation may aid in our understanding of these potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, the combination of amylin with other anorexigenic agents elicits additive (peptide YY , glucagon-like peptide 1 receptor agonism, phentermine and sibutramine) and even synergistic actions (leptin, cholecystokinin) to reduce food intake and body weight, illustrating the advantage of targeting multiple metabolic pathways to modulate body weight. [22][23][24][25] Importantly, clinical studies confirm the potential of amylin receptor agonism to promote weight loss. For example, pramlintide significantly reduced body weight in patients with diabetes on insulin therapy, an intervention associated with weight gain.…”
Section: Introductionmentioning
confidence: 90%
“…Because the analysis of the feeding microstructure is essential to assess the mechanisms regulating feeding behavior (18), we investigated the feeding pattern using a newly developed automated episodic food intake-monitoring device, which allows the undisturbed continuous monitoring during the dark phase with minimal human interference. This has been used in rats before (15,31,39,49) and was established recently for the use in mice (21,52). To investigate the specificity of the observed effects on feeding behavior, other behavioral parameters, such as grooming and locomotor activity, were assessed as established originally by Antin et al (1) and in our previous studies (50,53).…”
Section: ·Hmentioning
confidence: 99%